Wildlife killer instincts: human wildlife conflict and fatal incidents in Botswana - Israel R. Blackie; Ikanyeng Gaodirelwe; Charity Masole (Cogent Social Sciences)
This study adopted a mixed methods explanatory sequential research design to investigate predictors of the increased probability of human-wildlife conflicts (HWC) resulting in human injuries and fatalities. The first phase of the study involved analyzing secondary quantitative data collected over 10 years (2009-2019) from six wildlife districts (i.e. Ngamiland, Chobe, Kgalagadi, Central, South Central, and Gantsi) in Botswana. A logistic regression model was applied to assess the key variables of the study, including demographic, ecological/environmental, and geographic predictors of increased probability of fatality. Overall, the findings reveal that older victims, the winter season, Ngamiland Wildlife district, elephants (Loxodonta Africana), and distant health facilities present an increased probability of human fatality from animal attacks. In addition, rurality itself is a risk factor for the occurrence and severity of injuries. The second phase involved analyzing qualitative data which was used to explain the quantitative data. The results reveal that there is a need for increased public education and a holistic approach to wildlife conservation and management to reduce human casualties. The development of a human-wildlife conflict policy will ensure the comprehensive management of HWC issues in Botswana.